Pengaruh Deposito Mudharabah dan NPF Terhadap ROA dan Pembiayaan Bagi Hasil Sebagai Intervening pada Bank Umum Syariah - Anggita Rismawati Rachman; Benny Barnas; Ruhadi Ruhadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The researcher aims to discuss the factors that influence Return On Assets with the bank's internal variables as independent, namely Mudharabah Deposits, NPF and Profit Sharing Funding Value as intervening variables. To explain the direct and indirect effects of data analysis techniques used to use path analysis (Path Analysis) using SmartPLS 3.0 analysis software. The results showed that the Mudharabah Deposit had no effect, NPFt-1 had a negative effect and the Profit Sharing Funding Value had no effect on Return On Assets. Then Mudharabah Deposits do not have an effect on Return On Assets through Profit Sharing Financing Value and NPFt-1 has no effect on Return On Assets through Profit Sharing Financing Value. The novelty of the study with previous research is the existence of an analysis to find out what factors influence ROA and Value of Financing Sharing as an intervening variable.